IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH (SAK EMKM) DI INDONESIA: LITERATURE REVIEW - Yani, Muhammad; Zulkifli, Zulkifli (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to conduct a literature review on the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities in Indonesia. The method used is a literature review by analyzing various previous studies relevant to the implementation of these standards. The results show that the level of understanding and application of standards is still low to moderate, with the majority of business actors not yet consistently applying the standards. Factors influencing implementation include education level, business size, perception of benefits, government support, role of financial institutions, and availability of supporting infrastructure. The main challenges faced include low awareness, complexity of accounting language and terms, limited resources, minimal access to training, difficulty separating business and personal finances, and lack of continuous assistance. Consistent application of standards has a positive impact on the quality of financial reports, access to capital, managerial capabilities, and business sustainability. The study suggests the need for collaboration among various stakeholders in providing continuous education programs, intensive assistance, affordable technology infrastructure, and incentives to encourage standard adoption. Future research needs to focus on evaluating intervention effectiveness and in-depth studies in specific business sectors.